Tinjauan Normatif Kedudukan Lembaga Manajemen Kolektif Nasional (LMKN) sebagai State Auxiliary Organ berdasarkan Peraturan Pemerintah No. 56 Tahun 2021 tentang Pengelolan Royalti Hak Cipta Lagu dan/atau Musik - Mohamad Alen Aliansyah (Dialogia Iuridica, 2022)
The Government Regulation No. 56 of 2021 on Management of Song and/or Music Royalty (PP No. 56/2021) has given a huge impact in regulating National Collective Management Organization (LMKN) since it has given more detailed provisions for LMKN in terms of its definition, legal standing, and function than that on Ministry of Law and Human Rights No. 36 of 2018 on Procedures for Application and Issuance of Operational Permits and Evaluation of Collective Management Institutions. In PP No. 56/2021, LMKN has been defined as Lembaga Bantu Pemerintah (State Auxiliary Organ) and given authority to use its operational funds that come from royalties being collected by them. However, those provisions seem to be problematic as the previous basis regulation has not yet regulated the stipulations. By using stufentheorie created by Hans Kelsen and then developed by Hans Nawiasky, therefore, this research aims to know if the provisions of LMKN as State Auxiliary Organ and the authority given to LMKN to use operational funds from collected royalties as regulated in PP No. 56/2021 contradict with its ground norm. This research compares PP No. 56 of 2021 with Copyright Law and the other prevailing regulations and results that provisions of LMKN as a State Auxiliary Organ and the authority to use its operational funds are invalid. Therefore, the regulation needs to be harmonized to create a legal order. Keywords: National Collective Management Organization (LMKN), PP No. 56/2021, State Auxiliary Organ, Stufentheorie